2013
DOI: 10.1159/000353120
|View full text |Cite
|
Sign up to set email alerts
|

The Association between n-3 Polyunsaturated Fatty Acid Levels in Erythrocytes and the Risk of Rheumatoid Arthritis in Korean Women

Abstract: Background: Rheumatoid arthritis (RA) is one of the most common autoimmune diseases that result in chronic inflammation of the joints. n-3 polyunsaturated fatty acids (PUFAs) have been suggested to play a role in the pathogenesis and clinical course of RA. The purpose of the present study was to investigate whether erythrocyte levels of n-3 PUFA are associated with an increased risk of RA and whether this could potentially serve as an indicator of RA disease activity in Korean women. Methods: A total of 100 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
4
23
0
Order By: Relevance
“…In support of this hypothesis, a case-control study found RA cases had significantly lower levels of EPA, and EPA+DHA in their red blood cell (RBC) membranes (a biomarker of n-3 FA status) compared with controls. 32 Furthermore, we found both n-3 FA supplement use and n-3 FA levels in RBC membranes were inversely associated with anti-CCP2 positivity in individuals without RA, but at risk for future RA. 33 However, it remains unclear whether n-3 FA exposure is associated with other RA-related autoantibodies, such as RF, and whether the association between n-3 FAs and RA-related autoantibodies is modified by SE, similar to the effect modification observed between SE and smoking on RA.…”
Section: Introductionmentioning
confidence: 64%
“…In support of this hypothesis, a case-control study found RA cases had significantly lower levels of EPA, and EPA+DHA in their red blood cell (RBC) membranes (a biomarker of n-3 FA status) compared with controls. 32 Furthermore, we found both n-3 FA supplement use and n-3 FA levels in RBC membranes were inversely associated with anti-CCP2 positivity in individuals without RA, but at risk for future RA. 33 However, it remains unclear whether n-3 FA exposure is associated with other RA-related autoantibodies, such as RF, and whether the association between n-3 FAs and RA-related autoantibodies is modified by SE, similar to the effect modification observed between SE and smoking on RA.…”
Section: Introductionmentioning
confidence: 64%
“…In contrast to these findings, erythrocyte levels of α-linolenic acid (ALA; 18:3n3), EPA 20:5n3, and the omega-3 index (EPA plus DHA) were found to be significantly lower in RA patients compared to healthy controls in a Korean population, although diet was not accounted for in this study. In addition, EPA and ALA were negatively associated with the risk of RA in Korean women [212].…”
Section: Studies Of Beneficial Effect Of Diet In Ramentioning
confidence: 94%
“…↓ Risk of asthma, rhinitis and aeroallergen sensitization [200,204,220,221] ↓ Asthma symptoms scores and ↓ responsiveness to acetylcholine [222] Improvement in pulmonary functions and ↓ use of short-acting inhaled bronchodilators and inhaled corticosteroids [290] ↑ Prevalence of wheeze [248] Adulthood ↓ Prevalence of asthma symptoms, airway hyperresponsiveness and ↑ asthma control and lung function [47,202,206,207,224,[226][227][228]230,233] ↓ Exhaled nitric oxide, ↓ serum eosinophils and ↑ FEV1 [225,229] ↓ Bronchodilator use, ↓ exhale nitric oxide and ↓ severity of exercise-induced bronchoconstriction [228,[231][232][233] Allergic Rhinitis Infancy and childhood ↓ Risk of rhinitis development [251,[254][255][256] Adulthood ↓ Prevalence [257,258] Atopic Dermatitis Pregnancy and lactation ↓ Incidence and intensity in the offspring [259,260]…”
Section: Asthmamentioning
confidence: 99%
“…Patients with rheumatic diseases usually have lower levels of PUFAs in serum [290]. It has been demonstrated that serum lipid profile is also altered in other rheumatic diseases, such as polymyositis (PM), dermatomyositis (DM), and Sjögren Syndrome (SS) [298].…”
Section: Rheumatic Diseasesmentioning
confidence: 99%